Euro area money demand: empirical evidence on the role of equity and labour markets - Gabe de Bondt (European Central Bank (ECB), 2009)
This study presents empirical evidence on the long-run motives for holding euro area money by focusing on the role of equity and labour markets. Equity positively affects money demand through wealth effects, as equities are a significant store of household wealth and thus part of a financial transaction motive. Negative substitution effects through the expected return on equity reflect a speculative motive from the equity market. A precautionary motive from the labour market is captured by the annual change in the unemployment rate. The main conclusion is that equity and labour markets do matter for money. All three new elements, in particular housing and financial wealth, have been found statistically and economically significant in explaining M3 since 1983. These findings are robust across different proxies for the augmented motives and a shorter sample period starting in 1994.
Keywords: E41; G11; C32; 330; equity return; Euro area money demand; precautionary motive; wealth; Geldnachfrage; Portfolio-Management; Kapitaleinkommen; Zeitreihenanalyse; Eurozone; EU-Staaten